2014
DOI: 10.1063/1.4892890
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple-junction thin-film silicon-based solar cells with high open-circuit voltage

Abstract: We have fabricated a-SiOx:H/a-Si:H/nc-Si:H/nc-Si:H quadruple-junction thin-film silicon-based solar cells (4J TFSSCs) to obtain high spectral utilization and high voltages. By processing the solar cells on micro-textured superstrates, extremely high open-circuit voltages for photovoltaic technology based on thin-film silicon alloys up to 2.91 V have been achieved. Optical simulations of quadruple-junction solar cells using an advanced in-house model are a crucial tool to effectively tackle the challenging task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…A fundamental question addressed here is whether it is feasible to couple energy into a diffusion eigensolution, which has a greater energy density than that of the usual non-optimized energy density W d , as shown in figure 1(a). In case of light, an enhanced energy density inside the scattering medium is important for applications such in white LEDs [15][16][17][18], solar cells [19][20][21], random lasers [22][23][24], and biomedical optics [25].…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental question addressed here is whether it is feasible to couple energy into a diffusion eigensolution, which has a greater energy density than that of the usual non-optimized energy density W d , as shown in figure 1(a). In case of light, an enhanced energy density inside the scattering medium is important for applications such in white LEDs [15][16][17][18], solar cells [19][20][21], random lasers [22][23][24], and biomedical optics [25].…”
Section: Introductionmentioning
confidence: 99%
“…The same principle may also be applied to engineer the bandgap of hydrogenated amorphous silicon oxide and hydrogenated amorphous silicon carbide alloys which have the potential to achieve higher V oc than a-Si:H in solar cells. [34][35][36][37] FIG. 5.…”
mentioning
confidence: 97%
“…Recently, Si et al have shown an initial efficiency of 11.8% using an amorphous silicon oxide (a-SiO x :H) top cell. 10) Under certain assumptions, thin film silicon four-junction devices using different silicon alloys can yield conversion efficiency of up to 19.8% as has recently been predicted. 11) The significant improvement we were able to obtain in the present work, we ascribe mainly to the following aspects: (1) improved optoelectronic properties of the ZnO:Al front electrode, 12) (2) the use of an efficient µc-SiO x :H based intermediate reflector, 13) (3) the use of an improved multilayer top cell p-layer, 14,15) and (4) the use of a textured antireflective foil.…”
Section: Introductionmentioning
confidence: 84%